Effect of cage dimensions on welfare and production of farmed blue fox - Korhonen, Hannu T.; Orjala, Hanna (pl, 2010)
Comprehensive scientific interest has been to improve the housing environment of farmed foxes by both enriching the traditional cage and increasing its size (Mononen, 1996; Hovland and Bakken, 2000; Ahola, 2002; Koistinen et al., 2009). The results have shown that cage size per se has no or minimal essential value for animal welfare. It is, however, important that the housing cage should enable foxes to engage in behaviours such as escape, hiding, rest, watching the surroundings, play, gnawing, etc. These can be passably satisfied by offering the foxes platform and wooden block, both of which are now obligatory on farms (Korhonen et al., 2001 a, 2002). Our present study, in which the height of the cage was increased substantially, provides yet a further dimension to enrichment of the cage environment. The animal would have here more space to vertical behaviour if necessary. The animals grew well, remained healthy and produced good fur in all the experimental set-ups. Of the three options studied, the high cage seemed to be the least stressing. Further, because of the high roof, the foxes in a high cage are able to sit on the platform without the roof wearing down the fur on their backs. The extra height also makes it possible to attach another platform to the wall. Our conclusion is that the high cage is at least as suitable for housing foxes as is the traditional standard cage. This study was funded by the Finnish Fur Farmers' Association and MTT Agrifood Research Finland. The staff of the Fur Farming Research Station of Kannus (MTT) are gratefully acknowledged for their valuable help in carrying out this experiment
Keywords: Ko; sinikettu; Alopex lagopus; turkiseläimet; häkit; eläinten hyvinvointi; Alopex lagopus; furbearing animals; animal welfare; housing conditions; enlarged cage